Cadastro Territorial Multifinalitário (CTM), planejamento e gestão urbanos na Amazônia: a multifinalidade dos modelos de CTM de Belém e do Ministério das Cidades - ARAÚJO, Fernando Alves de (Universidade Federal do Pará, 2017)
The context of complexity, inequality and injustice of the capitalist urban space dates back to the need for a planning and management of this space considering these variables as intrinsic to this model of society, however without accepting them or defend them, having as the ultimate goal the urban development understood as promotion of life quality, social justice and autonomy for all those who produce, reproduce and live the urban space. This planner and manager practice should be perceived as an applied social research, interdisciplinary, covering an effective pipular participation, as well as use their various instruments to assess objectives satisfactorily. Among those instruments is the Cadastro Territorial Multifinalitário (CTM) - Territorial Multipurpose Cadastre, which although not a new idea, having its genesis dated millennia ago, and the current models being very close to those produced in Europe in the nineteenth century, Brazil count only with one "legislation" specifically geared to the CTM dated from the end of the first decade of this century, under an ordinance of the Ministrerio das Cidades - Ministry of Cities, which brought general recommendations about the structure and methodology of implementation of a model of cadastre. While in the local context, in Belém, Pará State Capital City, the production of records dating from the 1970s, and as the current one produced in 2000 as the Cadastro Técnico Multifinalitário.- Tecnical Multipurpose Cadastre. Thus, the present research aims to analyze, with some comparison, the model cadastre models of the Ministry of Cities, proposed in in its decree No. 511/09 - Cadastro Territorial Multifinalitário (CTM) - and the City of Belém Prefecture - called the Cadastro Técnico Multifinalitário, focusing on the issue of the multipurpose considered from the possibility of using the CTM in all spheres of urban planning and management, especially those not directly linked to tax and fiscal spheres, since these are historically the initial concerns of the cadastral record, configuring thus its purpose priority. The work was produced through the use of bibliographic search technique over authors who mainly discuss the concepts of space, territory, urban space, spatial planning, urban planning and management, with collect and analysis of secondary data, conducted through documentary research in official texts of the Ministerio das Cidades about the CTM model for it, its ordinance 511/09 which brought the guidelines of cadastre model, as well as execution reports of the Cadastro Técnico Multifinalitário de Belém and spreadsheets with information about the cadastre, provided by the managing agency of the CTM de Betém. Culminating with semi-structured interviews technique with experts from competent organs to the production and management of the CTM de Belém, as CODEM and SEFIN.